TINDAK TUTUR PEMIMPIN DALAM PERSPEKTIF MAKSIM KESOPANAN LEECH - Darmawan, Arief (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2021)
Abstract This research focuses on the speech acts of the leaders from various levels in Indonesia. To study this problem, the author uses Geoffrey Leech's politeness maxims theory which consists of the tact maxim, the generousity maxim, the approbation maxim, the modesty maxim, the agreement maxim, and the sympathy maxim. The data collection method used in this research is document study and literature study. The conclusion of this research is that most of the leaders in Indonesia have applied Leech's maxims of politeness optimally, especially the maxim of sympathy, which has led to a positive response from the people they lead. Leadership using verbal language that fulfills the maxims of politeness can be used as the basis for the next leader in managing the organization he leads, both large and small.